1987
DOI: 10.1136/hrt.57.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival and mode of death in severe chronic ischaemic cardiac failure.

Abstract: SUMMARY An evaluation of factors which may influence survival and mode of death was conducted over a three year period in a consecutive series of 50 patients with severe chronic ischaemic cardiac failure for more than three months. At the initial assessment all patients were already receiving intensive medical treatment. During follow up four patients successfully underwent cardiac surgery and medical treatment was modified in most patients, with four patients receiving antiarrhythmic drugs. Twenty six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 33 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…Left ventricular ejection fraction is one of the major predictors of survival in the analysis of heart disorders, and its drop results from cardiac dilation 19,32,33 . Some studies showed the efficacy in generating systolic force by surrounding the heart with muscular flaps 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular ejection fraction is one of the major predictors of survival in the analysis of heart disorders, and its drop results from cardiac dilation 19,32,33 . Some studies showed the efficacy in generating systolic force by surrounding the heart with muscular flaps 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found that the detection of an S3 has a high specificity and positive predictive value in detection of patients with low EFs [45]. Even more importantly, it has been suggested that patients with a detectable S3 have an increased risk of hospitalization and death compared with those patients without a detectable S3 [46][47][48].…”
Section: Significance Of S3 and S4 Detection In Heart Failurementioning
confidence: 96%
“…19 In another l-year, follow-up study of 69 patients with nonischemic dilated cardiomyopathy, ventricular arrhythmias were predictive of mortality with the highest mortality rates among those patients with the most severe arrhythmia^.^^ In a group of 62 patients with chronic CHF, those evidencing ventricular arrhythmias during baseline exercise testing had significantly lower 2-year survival rates than those who did not develop ventricular arrhythmias. "…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…Ventricular arrhythmias have been found in as many as 70% to 80% of patients with CHF and certain types and frequencies of ventricular arrhythmias have been shown to predict total mortality in heart failure?+ 19,29 In a study of 50 patients with chronic ischemic cardiac failure, mortality was highest in patients with serious ventricular arrhythmias on ambulatory electrocardiograms during both 1 -and 2-year follow-up periods. 19 In another l-year, follow-up study of 69 patients with nonischemic dilated cardiomyopathy, ventricular arrhythmias were predictive of mortality with the highest mortality rates among those patients with the most severe arrhythmia^.^^ In a group of 62 patients with chronic CHF, those evidencing ventricular arrhythmias during baseline exercise testing had significantly lower 2-year survival rates than those who did not develop ventricular arrhythmias.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation